Clinical and histologic characteristics of breast cancers in women with previous pathologic diagnosis of benign breast disease in Spain. Issue 4 (8th March 2018) - Román, Marta; Caicoya, Martin; Espinàs, Josep; Sala, Maria; Torá‐Rocamora, Isabel; Quinta, Maria J.; Vernet, Mar; Saladié, Francina; Romero, Anabel; Sánchez, Mar; Baré, Marisa; Vidal, Carmen; et al.
Abstract: Women with a benign breast disease (BBD) have an increased risk of subsequent breast carcinoma. Information is scarce regarding the characteristics of breast carcinomas diagnosed after a BBD. Our aim was to point out the differences in clinical and histologic characteristics of breast carcinomas diagnosed in women with and without a previous pathologic diagnosis of BBD in the context of population‐based mammography screening. Retrospective cohort study of all women aged 50‐69 years who were screened at least once in a population‐based screening program in Spain, between 1994 and 2011 and followed up until December 2012. The mean follow‐up was 6.1 years. We analyzed 6645 breast carcinomas, of whom 238 had a previous pathologic diagnosis of BBD. Information on clinical and histologic characteristics was collected from pathology reports. Logistic regression was used to estimate the odds ratio (OR) and 95% confidence intervals (95%CI) of occurrence of selected histologic characteristics of breast carcinomas in women with and without a previous BBD. Women with a previous BBD had a higher proportion of ductal carcinoma in situ (DCIS) compared with women without a BBD (22.1% and 13.6%, respectively). Among those diagnosed with an invasive breast carcinoma, women with previous BBD were more likely to be diagnosed with carcinomas sized >2 cm (OR = 1.46; 95%CI = 1.03‐2.08), metastatic positive (OR = 2.66; 95%CI = 1.21‐5.86), and with a high Ki‐67 proliferation rate (OR = 1.93; 95%CI = 1.24‐2.99). No differences were found across histologic subtypes of BBD. Screening participants with a previous pathologic diagnosis of BBD had a higher proportion of DCIS. However, invasive carcinomas detected in women with a BBD were associated with clinical and histologic characteristics conferring a worst prognosis.